PENGELOLAAN VISI, MISI, DAN TUJUAN SEKOLAH/MADRASAH DALAM MENINGKATKAN MUTU PENDIDIKAN DASAR - Arsyad Ashar; Muh Sadri; Anri Saputra; Kamus; Kurniawan; Munawir; Nurauliah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Schools and madrasas require a clear strategic direction so that educational programs do not stop at administrative routines. Vision, mission, and institutional objectives are essential instruments for aligning learning, school culture, resource management, and quality assurance. This article aims to describe the management cycle of developing, socializing, implementing, and evaluating school or madrasa vision, mission, and objectives as a basis for improving the quality of basic education. The method used is a literature study with a descriptive-analytical approach. Data were obtained from educational regulations, books on strategic management and school-based management, and relevant scientific articles. The analysis shows that vision and mission should be formulated through a participatory process based on internal and external context analysis. Socialization is effective when it uses formal, visual, digital, and participatory communication channels. Implementation must be translated into curriculum planning, learning practices, extracurricular activities, character formation, school culture, and institutional work programs. Evaluation should be conducted periodically using measurable indicators, evidence-based reflection, and follow-up plans. The contribution of this article is an integrated management cycle that connects strategic formulation, collective understanding, program execution, and continuous improvement in school and madrasa governance.